PATIENT SATISFACTION OVERVIEW OF NON-PRESCRIPTION DRUG SERVICES AT PHARMACY X, BANJARBARU - Nor Syipa Hayati; Juwita Ramadhani; Nily Su'aida (AL ULUM: JURNAL SAINS DAN TEKNOLOGI, 2025)
Quality pharmaceutical services play a key role in enhancing patient satisfaction, particularly in the provision of non-prescription medications at pharmacies. This study aims to present an overview of patient satisfaction with non-prescription drug services at X Pharmacy Banjarbaru. Using a quantitative descriptive design, data were collected through a questionnaire-based survey involving 354 respondents selected through purposive sampling based on specific criteria. Patient satisfaction was evaluated using the five servqual dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The dimensions of reliability, responsiveness, and assurance each achieved an average score of 84%, categorized as very satisfied. The empathy dimension reached 82%, while the tangibles dimension obtained 78%, both falling under the satisfied category. Overall, patients considered the services at x pharmacy Banjarbaru to be adequate. The study suggests improving dimensions that remain at the satisfied level and recommends further research to identify factors influencing patient satisfaction more comprehensively.